A construção da identidade do jesus negro em o auto da compadecida, de ariano suassuna: uma abordagem discursiva - Costa, Julia Cristina de Lima (2012)
In the context of discussions about the interfaces of Linguistics, analytical studies on literary productions have outstanded in the last years under the aegis of Discourse Analysis. In this research, we have concluded that the work O Auto da Compadecida by Ariano Suassuna, promotes an close approximation between the literary text and the biblical-theological text through the central figure of Christianity – Jesus. The main objective of this work is to analyze the identity of the black Jesus of O Auto da Compadecida in the light of Dialogical Discourse Analysis (DDA) with the identity of Jesus in the Gospels comparatively. The theoretical framework of the research articulates the concepts of Dialogical Discourse Analysis (DDA) about Dialogism, Polyphony and Carnivalization in literature as proposed by Bakhtin and the Circle and the Theory of the Cultural Studies based on the presuppositions of Stuart Hall (2006, 2008), Silva (2000), Gregolin (2008) and Bauman (2008), specifically concerning the conception of identity. Though with differentiated focuses, these theoreticians seem to point to the need of recognition of otherness in the discourses produced for the identity formation. This is a documental and bibliographical research of qualitative nature, guided by the interpretativist approach. The corpus is limited to the third act of the literary text – the judgment of the souls (celestial court). As for the results, we have observed that there is an intertextual and interdiscursive richness in the core of the literary piece studied. In this work, several discursive spaces get configured in an intense shock of voices in which they reveal themselves as naturally dialogical and polyphonical. We have also verified that, through the interdiscursive process, a few questions related to the sense of the inclusion of the black as a representative figure of Jesus as an icon of the holy one in the rewriting of the writer from Paraíba have been highlighted. Besides, the characterization of the black Jesus raises the discussion around social inclusion and exclusion and its ethical-religious implications which result from this discourse to society.